Pengaruh perputaran modal kerja, pertumbuhan penjualan dan ukuran perusahaan terhadap profitabilitas (Studi pada perusahaan properti yang terdaftar di Bursa Efek Indonesia tahun 2019-2022) - Runtuwene , Ellena Natasya; Sondakh, Jullie J.; Walandouw, Stanley K. (Riset Akuntansi dan Portofolio Investasi, 2023)
The purpose of this study is to determine the effect of Working Capital Turnover, Sales Growth, and Firm Size on Profitability in Property Companies listed on the Indonesia Stock Exchange in 2019-2022. This type of research is quantitative research using a sampling technique, namely purposive sampling. There are 30 sample companies selected from 85 companies. In this study, data were analyzed using multiple linear regression. The results of the analysis of this study partially working capital turnover and sales growth affect profitability. Meanwhile, firm size has no effect on profitability.